Benefit of targeted temperature management with amplitude integrated EEG for child - Uchino, Hiroyuki; Nagakura, Tomoki; Okita, Ayano; Okada, Toshio; Saiki, Iwao; Sekine, Shusuke (Japanese Journal of Reanimatology, 2022)
One-year-and eight month-old female child with Treacher Collins Syndrome who received cleft palate repair suffered from severe hypoxia due to the airway obstruction after extubation for 20min. Targeted temperature management (TTM) started with amplitude integrated EEG (aEEG) in order to prevent secondary hyoxic brain damage immediately. Four years after TTM, patient recovered without severe complication. We explored the usefulness of TTM with aEEG for neurocritical care management in the pediatric case with severe hypoxia.